Screening and Risk Factor Assessment of Cataract and Glaucoma in Hypertensive and Diabetic Populations along the Surabaya Coast - Irma Andriani Pasaribu; Aditya Wira Buana; Prawesty Diah Utami (Publication Department, Universitas Warmadewa, 2025)
Background: The coexistence of cataract, glaucoma, diabetes mellitus, and hypertension imposes a substantial ocular health burden in aging populations, especially in coastal communities exposed to ultraviolet radiation. Methods: This observational-analytical study evaluated the influence of hypertension and diabetes mellitus on the incidence of cataract and glaucoma among residents of Kedung Cowek, Surabaya (April 2025). Direct clinical examinations, demographic and medical histories, and ocular assessments were performed on all eligible patients presenting with blurred vision and documented hypertension or diabetes (total sampling). Results: Among 12 hypertensive patients along the Surabaya Coast, 8 (66.7%) had ocular abnormalities. Cataract was the most common finding (5 cases, 41.7%), followed by glaucoma (3 cases, 25%). Pterygium occurred in 4 cases (33.3%), likely linked to high UV exposure. Conclusion: Diabetes, and hypertension appears to accelerate cataract and glaucoma development in this coastal population. Oxidative stress from combined metabolic and environmental factors may overwhelm ocular defenses, increasing vision-related risk.